Metaliterature, self-censorship and satire in Francesco Pona's "Lucerna" (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
The paper investigates the relationship between metaliterature and satirical discourse within Francesco Pona’s Lucerna. Following the Giorgio Fulco’s studies about the presence of a prudential component in the dialogue, the essay deals with the ambiguities of the work, in order to verify if they are traces of an allusive discourse or mere ludic moments. In particular, the subject of this paper is a commentary on three programmatic passages with a pronounced self-censorial value. This comment discusses the evolution of the passages in the redactional phases of the Lucerna and the influence of two of the work's main models, John Barclay’s Argenis and Nicolò Franco’s Filena.
Keywords: Francesco Pona; Lucerna; satire; metaliterature